COVID-19: Pandemia E Seus Reflexos Nos Contratos De Trabalho Introduzidos Pelas Medidas Provisórias Nº 927/2020 E 936/2020 - Marinho, Luciana Nunes (Universidade Federal do Tocantins, 2022)
The social right to work is a constitutional guarantee based on the principle of protection and dignity of the human person. However, with the onset of the public health crisis as a result of sars-cov-2, the new corona virus, the concern with guaranteeing jobs and income led the Executive Branch to issue Provisional Measures number 927/2020 and 936/2020 , which in turn extrapolate the criticized labor reform approved in 2017, through law number 13.467/2017. Thus, the aforementioned diplomas are exorbitant with regard to the effectiveness of the individual agreement on the collective and, also on the legislated. Thus, in accordance with the principle of inescapability of jurisdictional protection, the Supreme Court analyzed the issue, which was also much discussed by the doctrine, around the provisions contained in the scope of the aforementioned provisional measures. Thus, this monographic essay aimed to analyze, with a focus on the control of conventionality and constitutionality, the applicability of MPs and their effects on employment contracts. The test method used was the deductive one, starting from a truth already known through bibliographical research and the understanding and positioning, signed by the Supreme Court.